Intra-household double burden of malnutrition in a North African nutrition transition context: magnitude and associated factors of child anaemia with mother excess adiposity. Issue 1 (9th October 2018) - Sassi, Sonia; Abassi, Mohamed Mehdi; Traissac, Pierre; Ben Gharbia, Houda; Gartner, Agnès; Delpeuch, Francis; El Ati, Jalila
Abstract: Objective: In the Middle East and North Africa region, the nutrition transition has resulted in drastic increases in excess adiposity, particularly among women, while some types of undernutrition remain prevalent, especially among pre-school children. We assessed the magnitude, nature and associated factors of the within-household co-occurrence of anaemia in children and excess adiposity in mothers. Design: Cross-sectional survey using stratified two-stage random cluster sampling to survey households with women aged 20–49 years. BMI≥25·0 kg/m 2 defined overweight and BMI≥30·0 kg/m 2 obesity, while anaemia for children was defined as Hb<110 g/l. The associations between child anaemia and mother excess adiposity, and sociodemographic and lifestyle factors were estimated by multinomial regression. Setting: Greater Tunis area, Tunisia, in 2009–2010. Subjects: Children aged 6–59 months living with their 20–49-year-old mothers (437 child–mother pairs). Results: The most prevalent double burden of malnutrition in child–mother pairs by far was the anaemic child and overweight mother (24·4 %; 95 % CI 20·1, 29·3 %). A significant proportion of pairs were anaemic child and obese mother (14·4 %; 95 % CI 11·0, 18·5 %). The co-occurrence of anaemia in child and excess adiposity in mother was neither synergetic nor antagonistic ( P =0·59 and 0·40 for anaemia–overweight and anaemia–obesity, respectively). This double burden was more frequent among child–mother pairs with younger children, with mothers of higher parity and higher energy intakes. Conclusions: The high prevalence of anaemic child and overweight or obese mother requires special attention e.g. through interventions which simultaneously target both types of malnutrition within the same household.